Comparison of Two Quality Analysis Checklists Used to Appraise Studies Regarding the Assessment of Auditory Processing Disorder in Older Adults - Ghosh, Vipin; Yathiraj, Asha; Devananda, Darshan (International Archives of Otorhinolaryngology, 2025)
Introduction A meta-analysis of published articles is usually done using standard scales and checklists. Several such scales and checklists are reported in the literature. However, there is little information regarding their utility so one can select the most appropriate one, especially in the field of audiology.Objective The current study aimed to compare a quality analysis carried out using the standard quality assessment criteria (SQAC) for evaluating primary research papers from a variety of fields', and the Modified Downs and Black Checklist (MDBC) for a set of articles in the area of auditory processing deficits (APDs) in older adults.Methods Two published checklists suitable for the field of audiology (SQAC and MDBC) were compared for a quality analysis of articles on APD in older adults. The two checklists were compared after categorizing their items into five subsections. Two audiologists rated the articles according to both checklists.Results The interrater reliability was found to be good for both checklists. Significant differences between the checklists were observed for specific subsections. However, there was no significant correlation between the two checklists.Conclusion It is inferred that the selection of an appropriate quality assessment checklist depends on the objective of the study. If the aim of a quality analysis study is to differentiate articles based on their overall caliber, or primarily based on the subsections, SQAC is recommended. However, if the aim is to distinguish research articles primarily based on the control of variables, or differentiate intervention-based studies, the MDBC is recommended.
Keywords: SQAC; MDBC; meta-analysis; systematic review